Putative functional SNPs in SLC22A3 and H3F3B might influence the development of CAD by regulating the lipid levels. Issue 168 (August 2018) - Mo, Xingbo; Zhang, Huan; Lei, Shufeng; Xu, Tan; Wang, Aili; Guo, Zhirong; Zhang, Yonghong
Highlights: Rs3103174, rs1050115 and rs1460816 were associated with TC levels ( P = 0.0368, 0.0403 and 0.0492, respectively). Rs3103174 in GLMN and rs2271308 in STARD3 were associated with LDL-C levels ( P = 0.0412 and 0.0196, respectively). Cis -eQTL effect was found for SNPs in GSK3B, SLC22A3, STARD3 and H3F3B . SNPs in SLC22A3 and H3F3B may influence lipid levels through altering the expression of local genes. SNPs in H3F3B may influence CAD risk through altering the expression of local genes. The decline in UBXN4 expression which results from the m 6 A-SNP rs1050115 might lead to familial hypercholesterolemia.